MERANCANG ROUTER INTERNET MENGGUNAKAN SISTEM OPERASI UBUNTU - Bersama Sinuraya; Peristiwa Ketaren (UPPM, 2017)
The internet is and the most important source for obtaining information. Internet is closely associated with the world of education. To meet and such facilities, it i s necessary to build a network router connected to the Internet network. The network is expected to be used for means of learning in particular education. This router network construction to continue functioning for a signal from the computer to another computer, as well as security tools such as firewalls are implemented through a router.